Studies on Closed-loop Interaction in a Multi-loop Single Tank Control System - Chourdhary, Abhijeet; Jain, Amit (International Journal of Engineering and Technology, 2018)
This paper investigates the interaction between level and flow loop in a single tank system. The data generated is used to generate all transfer functions via step test method. The model generated is then simulated on MATLAB-Simulink and the obtained results are then compared with experimental results for verification. A Relative Gain Array analysis is performed to check the interaction and comment on the pairing.Â Â